IMPACT OF SCHOOL READINESS INTERVENTION ON SCHOOL SKILLS OF CHILDREN WITH AUTISM SPECTRUM DISORDER (Contemporary Journal of Social Science Review, 2025)
This research aimed to evaluate the efficacy of school readiness intervention designed to prepare children with autism spectrum disorder (ASD) for school readiness. Using a pre-post research design, a purposive sampling technique was used to select 31 children aged 6 to 9 years diagnosed with ASD. Assessments were carried out using the childhood autism rating scale and school skills assessment protocol taken from the assessment of functional living skills at baseline and post intervention level. The findings at baseline and post intervention levels were compared and pre-post mean differences using paired sample t test were analyzed. The results of the current study showed that school readiness intervention significantly improved specific school skills of children with autism spectrum disorder. It is concluded that specific school readiness interventions  targeting specific school skills are useful for the children with ASD to improve their school readiness.